Elements of sustainable development in the export of bananas in Costa Rica from 2000 to 2018 - Mata Martínez, David (2023)
This research was carried out with the purpose of analyzing the productive processes involved in the export of fresh bananas in the Huetar Caribe zone, where there are connective axes between economic and social improvement that establish opportunities to achieve sustainable development in the industry. In this way, during the period from 2000 to 2018, an analysis strategy was executed based on the socioeconomic staggering approach widely used in other international value chains such as textiles and tourism. The approach had a qualitative character, where numerical data was taken as a starting point to later deepen through the methodological triangulation technique, which demanded the use of primary information obtained through 45 interviews applied in the main banana towns. The results show that the industry grew asymmetrically, obtaining a better economic result due to an increase in productivity, which did not require greater specialization in the existing labor force, an increase in the workforce, or the inclusion of new ones. places with higher added value, greatly limiting social improvement.